Interfaces entre a política de assistência social e a questão agrária: o perfil das famílias do assentamento da reforma agrária Padre Expedito e a atuação da equipe CRAS volante de Miranorte (TO) - Silva, Maria Aparecida Rodrigues da (Universidade Federal do Tocantins, 2022)
The objective of this study was to carry out a study on the profile of the families living in the rural setting of Padre Expedito, located in the municipality of Miranorte - TO, as well as to reflect the interfaces between the social assistance policy and the issue agrarian The research that has been carried out and the results presented here is justified by the need to demonstrate the importance of the Social Work professional in the daily lives of families, in the daily struggles generated by the various demands brought by these families. In order to carry out the survey on the profile of the families of the Padre Expedito settlement, we used documentary research based on the SUAS records of families and / or records of attendance / follow-up of the families living in the Fr. Expedito settlement from 2016 to 2018, containing data socioeconomic interviews conducted by Team CRAS Volante of the municipality of Miranorte (TO). The research was exploratory, with a qualitative approach of documentary analysis, we arrived at the approximate results that show that the non-production for the social support / reproduction of the families reveals agrarian reform plans that are not effective, being the families settled without support of a rural extension that actually cooperates with them. In order to access rights, we know of the need for professionals capable of making the mediations between families and existing policies, and the most important is that: without collective struggle, more hunger and other expressions of the social question.